1993
DOI: 10.1007/bf00987470
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of infochemicals from first and second trophic level in long-range host location by the larval parasitoidCotesia glomerata

Abstract: Recently parasitoids were hypothesized to encounter a reliability-detectability problem relating to chemical stimuli from the first and second trophic level, when searching for hosts. The relative role of infochemicals originating from the host,Pieris brassicae (second trophic level), and its food plant, cabbage (first trophic level), have been investigated with respect to long-range host location by the larval parasitoidCotesia glomerata. Flight-chamber dual choice tests showed that uninfested cabbage plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
87
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(95 citation statements)
references
References 33 publications
7
87
0
1
Order By: Relevance
“…The release of volatile compounds when plants are attacked by insect herbivores, and the attractiveness of such induced compounds to natural enemies, have been shown in various studies Steinberg et al, 1993;Geervliet et al, 1994;Dicke and Vet, 1998). In some systems, there are key compounds for the attraction of parasitoids, such as 6-methyl-5-hepten-2-one, which is an indicator of the presence of specific host aphids for the parasitoid, Aphidius ervi (Du et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The release of volatile compounds when plants are attacked by insect herbivores, and the attractiveness of such induced compounds to natural enemies, have been shown in various studies Steinberg et al, 1993;Geervliet et al, 1994;Dicke and Vet, 1998). In some systems, there are key compounds for the attraction of parasitoids, such as 6-methyl-5-hepten-2-one, which is an indicator of the presence of specific host aphids for the parasitoid, Aphidius ervi (Du et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Many plants attacked by herbivorous insects indirectly defend themselves by emitting semiochemicals that act as attractants for natural enemies of the attackers (Dicke and Sabelis, 1988;Turlings et al, 1990;Steinberg et al, 1993;Agelopoulos and Keller, 1994;Geervliet et al, 1994;Röse et al, 1997;Du et al, 1998;Shiojiri et al, 2000;Neveu et al, 2002). At least 12 families of plants produce volatiles in response to herbivory (Dicke, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that subtle differences in volatile profiles of uninfested plants could be important in the attractivity of these plants for D. semiclausum. Brussels sprout plants damaged by hosts are more attractive for the parasitoids Cotesia glomerata, C. rubecula, and C. plutellae than artificially damaged or intact Brussels sprout plants (Steinberg et al, 1992(Steinberg et al, , 1993Blaakmeer et al, 1994;Geervliet et al, 1996;Shiojiri et al, 2000). A recent study by Ohara et al (2003) showed that D. semiclausum females were attracted by the odor blends of uninfested and infested cruciferous plants.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies on host searching by parasitoids show that plant-provided cues are more important for the location of host habitats than odor cues from the host or host by-products (Turlings et al, 1990;Steinberg et al, 1993;McCall et al, 1993;Agelopoulos and Keller, 1994;Geervliet et al, 1994;Mattiacci et al, 1994;Takabayashi et al, 1995;Fukushima et al, 2002), but it remains largely unknown which compounds are the most crucial for the attraction.…”
Section: Introductionmentioning
confidence: 99%